IMPLEMENTATION OF WALIMATUL 'URS IN THE MIDDLE OF THE COVID-19 PANDEMIC A REVIEW OF MAQHASID SYARI'AH IN NEW VILLAGE COMMUNITIES DELI SERDANG DISTRICT - Novita Aulia Lubis; Jorge O. Brusa (Journal of International Islamic Law, Human Right and Public Policy, 2023)
Looking at it from the Maqashid Syari'ah perspective, government policy during the implementation of Community Activities was a form of Mashlahah (goodness)carried out to control the spread of the Covid-19 virus in order to create benefits for humans based on the M principleaqashid shariaIn it there is benefit for humans by protecting the five human existences including protecting the lives of hifd nafs.The creation of a benefit is basically by prioritizing the public benefit and can be seen in terms of the aim of Sharia', namely establishing that law always has a relationship, whether direct or indirect, and is related to the five basic principles of human life. Therefore, to find out the factors that are the reasons why people continue to hold luxurious Walimatul 'urs receptions in the midst of the Covid-19 pandemic, this research was prepared using normative-empirical research methods and a statute approach and a case approach. . There are three legal materials used, namely primary, secondary and tertiary legal materials. then the three legal materials were collected using the observation method through interviews supported by data and processed using qualitative methods and described using deductive logical thinking. And it was found that the Governor's Instructions had not been fully implemented by the community, Walimatul 'Urs was still being carried out as usual without taking into account the Covid-19 season and not implementing the recommended health protocols. The Government must provide more specific provisions and sanctions for regional (per region) because the development of the virus in each region is very different.